2003
DOI: 10.1117/12.482582
|View full text |Cite
|
Sign up to set email alerts
|

Property of single-crystalline Si TFTs fabricated with μ-Czochralski (grain filter) process

Abstract: Formation of TFTs inside location-controlled large Si grains with a low temperature process is an attractive approach for realizing system-circuit integration with displays on a large glass substrate. Local structural variations of the substrate using photolithography allows an accurate location-control of the large Si grains in excimer-laser crystallization. Single-crystalline Si (c-Si) TFTs was formed inside a location-controlled large (6 µm) grain by µ-Czochraski process of a-Si film. The c-Si TFTs showed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Furthermore, the location-controlled grain has planar defects, which are mainly coherent 3 twin boundaries and are radially distributed from the grain filter center. It has been suggested that the defective planes that are perpendicular to the current flow direction impede the ON-current [13]. In this paper, we have fabricated TFTs with and without a grain filter and with various current flow directions.…”
mentioning
confidence: 99%
“…Furthermore, the location-controlled grain has planar defects, which are mainly coherent 3 twin boundaries and are radially distributed from the grain filter center. It has been suggested that the defective planes that are perpendicular to the current flow direction impede the ON-current [13]. In this paper, we have fabricated TFTs with and without a grain filter and with various current flow directions.…”
mentioning
confidence: 99%